Studies on the participation of epididymal sperm protein DE/CRISP-1 in egg activation - Busso, D. (2003)
Protein DE (32 kDa) associates with sperm during epididymal maturation and participates in sperm-egg fusion through its binding to complementary sites on the egg surface. In the present work we investigated the participation of DE in two mechanisms probably involved in egg activation: the ability of DE to trigger activation by its interaction with the binding sites on the egg surface (receptor model) and its ability to regulate intracellular calcium channels (sperm factor model). The incubation of eggs with DE did not promote activation parameters such as calcium oscillations or meiosis resumption. Secondly, microinjection of DE into eggs was ineffective in either eliciting calcium release or modifying oscillations induced by an activating sperm extract. Together, these results argue against the participation of DE in egg activation, restricting the activity of this protein and its egg binding sites to the sperm-egg fusion process.